Step
*
2
1
of Lemma
qsum-linearity2
1. ∀d:ℕ
     ∀[a,b:ℤ].
       ∀[X,Y:{a..b-} ⟶ ℚ].  (Σa ≤ i < b. X[i] + Y[i] = (Σa ≤ i < b. X[i] + Σa ≤ i < b. Y[i]) ∈ ℚ) supposing (b - a) ≤ d
2. a : ℤ
3. b : ℤ
4. X : {a..b-} ⟶ ℚ
5. Y : {a..b-} ⟶ ℚ
6. a ≤ b
⊢ Σa ≤ i < b. X[i] + Y[i] = (Σa ≤ i < b. X[i] + Σa ≤ i < b. Y[i]) ∈ ℚ
BY
{ (InstHyp [⌜b - a⌝] 1⋅ THEN Auto) }
Latex:
Latex:
1.  \mforall{}d:\mBbbN{}
          \mforall{}[a,b:\mBbbZ{}].
              \mforall{}[X,Y:\{a..b\msupminus{}\}  {}\mrightarrow{}  \mBbbQ{}].    (\mSigma{}a  \mleq{}  i  <  b.  X[i]  +  Y[i]  =  (\mSigma{}a  \mleq{}  i  <  b.  X[i]  +  \mSigma{}a  \mleq{}  i  <  b.  Y[i])) 
              supposing  (b  -  a)  \mleq{}  d
2.  a  :  \mBbbZ{}
3.  b  :  \mBbbZ{}
4.  X  :  \{a..b\msupminus{}\}  {}\mrightarrow{}  \mBbbQ{}
5.  Y  :  \{a..b\msupminus{}\}  {}\mrightarrow{}  \mBbbQ{}
6.  a  \mleq{}  b
\mvdash{}  \mSigma{}a  \mleq{}  i  <  b.  X[i]  +  Y[i]  =  (\mSigma{}a  \mleq{}  i  <  b.  X[i]  +  \mSigma{}a  \mleq{}  i  <  b.  Y[i])
By
Latex:
(InstHyp  [\mkleeneopen{}b  -  a\mkleeneclose{}]  1\mcdot{}  THEN  Auto)
Home
Index